Ethical Framework On Breast Self-Examination System - Khana, Rajes (2022)
Breast Cancer is the leading cause of mortality for females in Indonesia. There is a need for women in Indonesia to have a breast self-examination system (BSE) where they can seek information and consult their cases with any physician; However, violation of patient confidentiality, lack of patient trust in physician conduct, and lack of patient control over their data pose a major problem in the use of BSE system. For this reason, there is a need to design a BSE system that can track self-exam data and allow communication between patient and physician. In developing a BSE system, ethical and trustworthiness values should exist as a part of the system’s ability. A survey was conducted to identify the ethical and trustworthiness values that can be applied to the BSE system. Therefore, this research aims to identify ethical values, determine the suitable trustworthiness factors, and propose an ethical framework that suits the development of the BSE system. The explanatory mixed-method carried quantitative survey with 772 respondents. A qualitative focus group discussion is conducted with 32 participants leading to the importance of an ethical framework being used in the healthcare system. The findings indicate that ethical values positively influence the BSE system with a pvalue < 0.001, trustworthiness positively influences the BSE system with a p-value < 0.001, and an ethical framework is essential to implement in the BSE system due to the coefficient of determination (R2) = 0.509.